Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1529/biophysj.107.107557
|View full text |Cite
|
Sign up to set email alerts
|

R-92L and R-92W Mutations in Cardiac Troponin T Lead to Distinct Energetic Phenotypes in Intact Mouse Hearts

Abstract: It is now known that the flexibility of the troponin T (TnT) tail determines thin filament conformation and hence cross-bridge cycling properties, expanding the classic structural role of TnT to a dynamic role regulating sarcomere function. Here, using transgenic mice bearing R-92W and R-92L missense mutations in cardiac TnT known to alter the flexibility of the TnT tropomyosin-binding domain, we found mutation-specific differences in the cost of contraction at the whole heart level. Compared to age- and gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 23 publications
(40 reference statements)
4
61
1
Order By: Relevance
“…Another study on energy utilization in TnT-FHC showed that transgenic hearts with R92W and R92L TnT mutations both showed greater ATP utilization during muscle contraction, with the R92W hearts showing more severe energetic abnormalities and greater contractile dysfunction than the R92L hearts (81). These hearts had higher intracellular ADP and P i levels, as well as lower ATP and phosphocreatine levels (81). It was shown in our study that the levels of creatinine were higher in I79N hearts than WT hearts.…”
Section: Proteins Involved In Metabolism-supporting
confidence: 56%
“…Another study on energy utilization in TnT-FHC showed that transgenic hearts with R92W and R92L TnT mutations both showed greater ATP utilization during muscle contraction, with the R92W hearts showing more severe energetic abnormalities and greater contractile dysfunction than the R92L hearts (81). These hearts had higher intracellular ADP and P i levels, as well as lower ATP and phosphocreatine levels (81). It was shown in our study that the levels of creatinine were higher in I79N hearts than WT hearts.…”
Section: Proteins Involved In Metabolism-supporting
confidence: 56%
“…Hearts were isolated and perfused in the Langendorff mode as described previously (23). The hearts were excised from 5-to 6-mo-old cVLCAD ϩ/ϩ (n ϭ 13) and cVLCAD…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of heart function by MRI was performed on anesthetized mice using gated Flash-CINE sequences. Langendorff perfusion was performed as described previously (34).…”
Section: Figurementioning
confidence: 99%